2014
DOI: 10.1002/term.1939
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term in vivo assessment of bioengineered skin substitutes: a clinical study

Abstract: The aim of the study was an objective in vivo assessment of skin properties after reconstruction with two artificial dermal substitutes, Integra ® and Hyalomatrix ® . Twenty-seven patients underwent reconstruction of 36 skin-loss sites with full-thickness skin graft, split-thickness skin graft, Hyalomatrix ® bioengineered skin substitute and sequential split-thickness skin graft and Integra ® bioengineered skin substitute and sequential split-thickness skin graft. Objective assessments were carried out using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 27 publications
2
41
2
Order By: Relevance
“…The majority of skin grafts lead to hypopigmented skin compared to normal uninjured skin[146]. The addition of melanocytes into skin substitutes has been effective in being able to alter the healed skin’s natural colour[147].…”
Section: Components Of a Skin Substitutementioning
confidence: 99%
See 1 more Smart Citation
“…The majority of skin grafts lead to hypopigmented skin compared to normal uninjured skin[146]. The addition of melanocytes into skin substitutes has been effective in being able to alter the healed skin’s natural colour[147].…”
Section: Components Of a Skin Substitutementioning
confidence: 99%
“…These effects on cellular differentiation and mechanotransduction suggests that the matrix for skin substitutes should be similar in stiffness and elasticity as native skin and perhaps promotes the use of different matrices for different areas of human skin. However, although studies have shown skin post-wound healing can have different resulting elasticities when treated with different skin substitutes[146], it is still unknown whether the elasticity of the skin substitutes directly affects the final resulting skin elasticity or whether it is another component or characteristic of the skin substitute. The degree of swelling and elasticity of a hydrogels is dependent on the types of polymers in the hydrogel such as elastin which has previously been mentioned, cross-link density, and polymer concentration.…”
Section: Creating Skin Substitutesmentioning
confidence: 99%
“…Whole skin (epidermal and dermal) thickness and density with a 2‐mm‐diameter probe could visualize that the dermal layer contained more vessels compared with the control group after transplantation, along with healthy skin. (Nicoletti et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding skin reconstruction, the regeneration of the epidermis by a cultured epidermal autograft (CEA) using Green’s method was established in the 1970s [10]. A method of dermal regeneration that achieves sufficient strength and elasticity has not yet been established [11,12]. …”
Section: Introductionmentioning
confidence: 99%